2018
DOI: 10.3847/1538-4357/aaa082
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Accretion onto a Non-magnetized Neutron Star: Why is it Feasible?

Abstract: To understand why supercritical accretion is feasible onto a neutron star, we carefully examine the accretion flow dynamics by 2.5-dimensional general relativistic (GR) radiation magnetohydrodynamic (RMHD) simulations, comparing the cases of accretion onto a non-magnetized neutron star (NS) and that onto a black hole (BH). Supercritical BH accretion is relatively easy, since BH can swallow excess radiation energy, so that radiation flux can be inward in its vicinity. This mechanism can never work for NS which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…Numerical simulations, although very impressive, cannot be of much help (even if they discuss the "spherization radius"). Instead of an external thin disc, they have a torus (Takahashi & Ohsuga 2017;Takahashi, Mineshige & Ohsuga 2018;Abarca, Kluźniak & Sadowski 2018). The critical radii are uncertain by no more than factors ∼ 1, so we expect (as here) the results of KLK17 will remain robust in comparison with both observations and future numerical simulations.…”
Section: Discussionmentioning
confidence: 51%
“…Numerical simulations, although very impressive, cannot be of much help (even if they discuss the "spherization radius"). Instead of an external thin disc, they have a torus (Takahashi & Ohsuga 2017;Takahashi, Mineshige & Ohsuga 2018;Abarca, Kluźniak & Sadowski 2018). The critical radii are uncertain by no more than factors ∼ 1, so we expect (as here) the results of KLK17 will remain robust in comparison with both observations and future numerical simulations.…”
Section: Discussionmentioning
confidence: 51%
“…The last work shows that supercritical accretion is possible even on a neutron star that has no magnetic field at all. Based on the MHD calculations, Takahashi et al (2018) showed that in this case an accretion disk should have a structure generally similar to that described in the Introduction of this review (i.e., a conical funnel with H ∼ R filled with rarefied gas moving at relativistic velocities), but having a more powerful wind. Near the surface of a neutron star, the gas stops and a "cushion" consisting of matter and radiation is formed.…”
Section: Ultraluminous X-ray Pulsarsmentioning
confidence: 77%
“…In addition to models with strong magnetic fields, another class of models have been proposed the presence of magnetar fields is not required to explain the ULXP phenomenon, and large observed luminosities is attributed to high collimation (King andLasota, 2016, 2019 (Takahashi et al, 2018). The last work shows that supercritical accretion is possible even on a neutron star that has no magnetic field at all.…”
Section: Ultraluminous X-ray Pulsarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, in the case of accretion onto NS magnetic poles, the accretion column is expected to be responsible for the emission at high energies (Walton et al 2018a). Unfortunately, simulated spectra from super-critically accreting NSs from numerical simulations are still under study (e.g., Takahashi & Ohsuga 2017;Takahashi et al 2018) and it is currently hard to know how the emission from the accretion column reacts to changes in the mass-transfer rate and magnetic field strength. Nevertheless, if the accretion column is responsible for the stable emission observed in these sources, it is still unclear why we observe this difference in terms of stability between PULXs and sources like NGC 1313 X-1 and Holmberg IX X-1.…”
Section: Origin Of the High-energy Tailmentioning
confidence: 99%